Asuhan Kebidanan Komprehensif Dengan Kehamilan Normal Di Puskesmas Bontonyeleng Tahun 2023 - Nurhalisa, Nurhalisa; Nurlaily, Andi; Asmirati, Asmirati; Fajriani, A. Tenri; Risnawati, Risnawati (Jurnal Medisains Kesehatan, 2023)
Pregnancy, childbirth, and the postpartum period are normal for a mother. However, it may turn out to be abnormal because of several complications that cause MMR and IMR such as bleeding, high blood pressure, or preeclampsia, postpartum infection, lack of routine maternal visits during pregnancy and in neonates shortness of breath, weak body condition, yellowish skin. So that more effective service efforts need to be made, namely by providing comprehensive midwifery care where this care is expected to be able to detect early complications that occur from pregnancy to family planning with the hope that the mother is able to go through the process normally. The purpose of this study was to provide comprehensive care to Mrs "R" aged 24 years starting during pregnancy until the use of family planning. The method used in conducting comprehensive midwifery care is a qualitative method with a case study approach (case study) Varney method with data collection techniques including observation, interviews, physical examination and documentation studies. The results of this study can be concluded, that comprehensive midwifery care on Mrs "R" with normal pregnancy has been known from the results of observations that indicate no problems since the care was carried out starting from the gestational age of 36 weeks 2 days until giving birth to the second child with a body weight of 4000 grams, body length 50 cm, male gender. The conclusion of comprehensive midwifery care on Mrs "R" was carried out according to midwifery care standards with normal results without any complication.